The ICT and reading promotion in teenagers. A case study from the beliefs of teachers - Manuel Francisco Romero Oliva; Hugo Heredia Ponce; Ester Trigo Ibáñez (Universidad de La Rioja, 2020)
This paper, proposed as a case study from a mixed approach of mediation, aims to analyze teachers' beliefs about the integration of ICT in teaching-learning processes for the promotion of reading. The studied context is focused in a High School center situated in Cádiz. It counted with the participation of 14 teachers (N = 14) -linguistic areas (n = 6) and non-linguistic (n = 8) - To understand the reality analyzed, it was necessary to combine quantitative instruments (questionnaire of beliefs and attitudes of teachers), and qualitative (focus groups). The results, collected through a SWOT matrix, although they reflect a proactive attitude of the teacher towards educational innovation for the adolescent's reading promotion, show a formative need to face this challenge from a vision of an educational center.